Generalized Euler‐Knopp method and convergence acceleration - Meronen, O.; Tammeraid, I. (Mathematical Modelling and Analysis, 2006)
New propositions on λ‐boundedness for generalized Euler‐Knopp method of summability (ϵ, T), where ? is a linear bounded operator from Banach space X into X, are proved. Using these results are verified a proposition on convergence acceleration by (ϵ, T) and a Tauberian remainder theorem for (ϵ,T).First Published Online: 14 Oct 2010